2021
DOI: 10.2147/copd.s307192
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pulmonary Fibrosis Emphysema: Role of Cigarette Smoking and Pulmonary Hypertension in a Rural Cohort

Abstract: Background Disease heterogeneity in idiopathic pulmonary fibrosis (IPF) often complicates the systematic study of disease, management of patients and clinical investigations. Objective To describe combined pulmonary fibrosis emphysema (CPFE) phenotype in a rural Appalachian IPF cohort with the highest smoking rates in the United States. Methods CPFE patients (n = 60) in a developed IPF cohort (n = 153) were characterized. Groups (CPFE vs IPF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Moderate to severely reduced DL CO is a consistent and characteristic finding mentioned in CPFE patients reflecting the additive effects of emphysema and fibrosis on the reduction in surface area available for gas exchange [ 46 ]. A greater exposure to cigarette smoke and reduced DL CO were predictors for CPFE in a cohort of IPF patients [ 16 ]. Similar deleterious effect of emphysema in patients with interstitial features were reported by Ash SY et al based on limited availability of DL CO findings in their study participants (< 5%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate to severely reduced DL CO is a consistent and characteristic finding mentioned in CPFE patients reflecting the additive effects of emphysema and fibrosis on the reduction in surface area available for gas exchange [ 46 ]. A greater exposure to cigarette smoke and reduced DL CO were predictors for CPFE in a cohort of IPF patients [ 16 ]. Similar deleterious effect of emphysema in patients with interstitial features were reported by Ash SY et al based on limited availability of DL CO findings in their study participants (< 5%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Appalachian region is challenged with the highest rates of smoking (25.2%) in the United States [ 14 ]. Subsequently, there is an excessive burden of lung disease associated with smoking in this region [ 15 , 16 ]. Employing a cohort diagnosed with lung nodule/mass and undergoing surgical resection, we (1) define the prevalence of ILAs/ILDs, (2) delineate clinical, radiographic and pathologic predictors of ILAs/ILDs, and (3) determine their associations with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…CSE is a risk factor for the development of lung fibrosis [ 65 ]. Renal fibrosis is involved in various kidney diseases [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,31,32 Some studies found that patients with CPFE had higher RVSP, or more large pulmonary trunk size, which were hemodynamic and radiological signs of PH, respectively. [33][34][35] Additionally, in our meta-analysis, different cutoffs of esPAP to diagnose PH were used in the selected studies. Thus, a subgroup analysis was conducted, and the results demonstrated the highest risk of PH with esPAP thresholds ≥ 50 mm Hg, a higher risk with a cutoff between 40 and 50 mm Hg, and a non-signi cantly high risk with a cutoff between 30 and 40 mm Hg in patients with CPFE compared with patients with IPF alone.…”
Section: Discussionmentioning
confidence: 99%